Retraction note: EGFR Targeted Paclitaxel and Piperine Co-loaded Liposomes for the Treatment of Triple Negative Breast Cancer (AAPS PharmSciTech, (2020), 21, 5, (151), 10.1208/s12249-020-01671-7) - Burande A.S.; Viswanadh M.K.; Jha A.; Mehata A.K.; Shaik A.; Agrawal N.; Poddar S.; Mahto S.K.; Muthu M.S. (My University, 2025)
The Editors-in-Chief have retracted this article because, after the publication of the article, a reader raised concerns about partial image overlap between Figure 3a (ii) and Figure 1B (iii) of [1]. The authors stated that they found similarities in Figure 3b(i) and 3b(ii), and therefore provided raw images for Figures 3a, 3a(ii), 3b(i), and 3b(ii). Further investigation of raw images by the publisher found that the raw images for Figures 3a(ii), 3b(i), and 3b (ii) do not match with published images. Therefore, the Editors-in-Chief have lost confidence in the data presented in the article. None of the authors responded to any correspondence from the editor/publisher about this retraction. © American Association of Pharmaceutical Scientists 2024.